Clinical Characteristics and Treatment Outcome of Langerhans Cell Histiocytosis: 22 Years' Experience of 154 Patients at a Single Center. (1st April 2014) - Lee, Ji Won; Shin, Hee Young; Kang, Hyoung Jin; Kim, Hyery; Park, June Dong; Park, Kyung Duk; Kim, Han-Soo; Park, Sung-Hye; Wang, Kyu-Chang; Ahn, Hyo Seop
<x xml:space="preserve">Abstract</x> Langerhans cell histiocytosis (LCH) is a rare disease of unknown etiology. Large studies by single institutions have been infrequent because of the rarity of the disease and the diversity of clinical manifestations. In this study, the clinical characteristics, prognostic factors, and treatment outcomes were analyzed. Medical records were analyzed retrospectively for the 154 patients diagnosed and treated with LCH at Seoul National University Children's Hospital from January 1986 to December 2007. A total of 154 patients were evaluated. One hundred and six patients (68.8%) had single system disease, 48 patients (31.2%) had multisystem disease. Twenty-nine patients (18.8%) had risk organ involvement. Twenty-nine patients (18.8%) relapsed and the overall survival (OS) of the total study population was 97.1% with a median follow-up period of 7.0 years. Patients less than 4 years old, with involvement more than 2 organs and with risk organ involvement showed lower progression free survival (PFS) (P = .001, <.001, and <.001, respectively). Estimated 10-year PFS of patients with and without risk organ involvement were 52.6% and 83.8%, respectively. Patients with single system LCH had excellent prognosis showing 89.6% of PFS and 100% of OS. Patients with multisystem LCH also had a high survival rate, although the incidences of relapse remain to be solved. A new strategy to decrease the incidence of relapse is needed.